THE MAKING OF A PROFILE BOOK OF TOURISM OBJECTS IN MERANTI ISLANDS REGENCY - Nuraini Nuraini; Rionaldi Rionaldi (INOVISH JOURNAL, 2017)
Abstract: Meranti Islands Regency is one of the biggest sago producers in Indonesia. In addition, it Â also has much potency in tourism sector. However, the potency it has is not been explored well. The main purpose of this study was to make a profile book about tourism objects in Meranti Islands Regency as a media of promotion to promote tourism objects in Meranti Islands Regency. This profile book discusses about water war festival, shell seeking with a plank, Beting Beras beach, the Darul Ulum grand mosque, Sejahtera Bakti Buddhist monastery, Â Kue Bulan festival, â€œImlekâ€ Chinese new year celebration, and Bokor cultural tourism village. Hopefully, this profile book can give more information for local people, tourists, and also help Department of Tourism, Youth, and Sport of Meranti Islands Regency in promoting tourism objects in Meranti Islands Regency.Â Keywords: Meranti Islands Regency, Profile Book, Promotion